Educational Planning and Preparation Process - Ivanuš Grmek, Milena; Mithans, Monika (Sodobni didaktični diskurzi v kontekstu pedagoške tradicije: Monografija v počastitev 80-letnice prof. dr. Martina Kramarja, 2025)
This paper examines the theoretical and practical dimensions of planning the educational process through a qualitative analysis of Dr. Kramar’s professional and scholarly contributions. It outlines three levels of teacher planning-global, stage-based, and immediate-emphasizing their distinct roles in designing instruction that is both pedagogically sound and effective. Kramar’s conceptual framework is further enriched by incorporating insights from selected didactic literature, thereby situating his ideas within the context of contemporary educational discourse. Rather than presenting empirical findings, the paper offers a structured analysis of core theoretical principles to encourage reflection and professional evaluation of didactic planning in educational practice.